P508 Dose adjustment in patients with moderate to severe ulcerative colitis: results from year 3 of the UNIFI maintenance study long-term extension. (27th May 2021) - Rowbotham, D S; Scherl, E J; Sands, B E; Panaccione, R; Peyrin-Biroulet, L; Zhang, H; Miao, Y; Leong, R W; Afif, W; Arasaradnam, R P; Danese, S; Marano, C
Abstract: Background: The UNIFI randomized-withdrawal maintenance study and long-term extension (LTE) evaluated the safety and efficacy of subcutaneous (SC) ustekinumab (UST) in patients with moderately to severely active ulcerative colitis (UC) who had responded to intravenous (IV) UST during induction. We evaluated the efficacy of UST dose adjustment through Week (Wk) 152 of the long-term extension (LTE). Methods: 523 intravenous UST induction responders were randomized to SC maintenance therapy (SC placebo [PBO], n=175; UST 90mg every 12 weeks [q12w], n=172; or UST 90mg q8w, n=176). 284 UST patients who completed wk44 entered the LTE. PBO patients were discontinued after wk44 unblinding. Based on the investigator's clinical judgement of their UC disease activity, patients in the LTE were eligible to receive dose adjustment starting at Wk 56: PBO to q8w, q12w to q8w, and q8w to q8w (sham adjustment). Patients in PBO or q8w groups were only eligible for dose adjustment or sham dose adjustment before unblinding. Patients were assessed for symptomatic remission, partial Mayo scores, and inflammatory markers ≥16 wks after dose adjustment. Results: Overall, 60 patients (42.6%) in the q12w group and 40 patients (28.0%) in the q8w group underwent dose adjustment (or sham dose adjustment) prior to Wk 156 of the LTE; 51 and 39 patients in each group, respectively, had dose adjustment at Wk 136 or before, providing≥16 wks of data after dose adjustment (Table). At the first visit ≥16 weeks after dose adjustment, 70.6% of patients who adjusted from q12w to q8w and 61.5% who sham dose adjusted from q8w to q8w were in symptomatic remission. At the time of dose adjustment, 27/51 patients (52.9%) in the q12w group and 25/39 patients (64.1%) in the q8w group were in symptomatic remission. Of those who were in symptomatic remission at the time of dose adjustment, the majority (81.5% and 68.0%, respectively) were maintained in symptomatic remission at the first visit ≥16 wks after dose adjustment. Of those who were not in symptomatic remission at the time of dose adjustment, 58.3% and 50.0%, respectively, were in symptomatic remission at the first visit ≥16 wks after dose adjustment. Mean partial Mayo scores and CRP levels decreased after dose adjustment (Table). Conclusion: Patients may benefit from UST dose adjustment to q8w.